On the fracture statistics of open-porous alumina foam structures. Issue 5 (May 2022) - Neumann, Marc; Hubálková, Jana; Voigt, Claudia; Grabenhorst, Joern; Aneziris, Christos G.
Highlights: The impacts of the specimen height to width ratio and loading rate on the strength of alumina foam structures were shown. For repeatable bending measurements, specimens of a low height to width ratio (< 0.5) were found to performed best. The Normal distribution yielded a suitable representation of scale and scatter of the strength of alumina foam structures. A standard Weibull analysis stood behind the Normal distribution analysis. Abstract: In the present study, industrial fabricated alumina foams of three different cell sizes were under study in terms of compressive and bending strength. Questioned were the impact of the cell dimensions and, in terms of bending strength, the loading rate and the specimen aspect ratio. The foam structures were characterised by the aid of micro focus X-ray computer tomography and analysed by optical microscopy. By normalising and averaging the load-displacement curves, the foam elasticity was analysed. The resulting sets of strength data were compared by the aid of four different probability distributions, namely the Normal, Log-Normal, Weibull, and Gamma distribution. For most of the test sets of the open-porous alumina foams, either the Normal or the Log-Normal distribution proved the best representation of the strength data.